2021
DOI: 10.1016/j.jamcollsurg.2021.07.170
|View full text |Cite
|
Sign up to set email alerts
|

Doubts About Cutting It Out: Systematic Review and Meta-analysis of Patient-Centered Outcomes in Nonoperative Management vs Surgery in Acute Uncomplicated Appendicitis in Adults

Abstract: INTRODUCTION:The majority of individuals who become opioid dependent receive their first opioid prescription after a surgical procedure. While studies suggest optimal pain management after surgery should include opioid-sparing adjuncts, it is unclear if inhospital opioid-sparing prescribing influences discharge opioid prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Indeed, several recent prospective randomized control trials both in Europe and the USA have demonstrated non-inferiority of antimicrobial-based pharmacologic management of early-stage acute appendicitis compared with appendectomy [15][16][17][18][19]. While these results have been met with great interest, and have provided therapeutic alternatives in the appropriate patient, the incidence of recurrent acute appendicitis, principally in patients with an appendicolith, ranging from 24 to 31%, is seen by some as a failure of non-operative management [20,21]. Thus, outcomes related to surgical removal of the appendix remain of great importance for surgeons, Emergency Medicine clinicians, Primary Care physicians, as well as patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several recent prospective randomized control trials both in Europe and the USA have demonstrated non-inferiority of antimicrobial-based pharmacologic management of early-stage acute appendicitis compared with appendectomy [15][16][17][18][19]. While these results have been met with great interest, and have provided therapeutic alternatives in the appropriate patient, the incidence of recurrent acute appendicitis, principally in patients with an appendicolith, ranging from 24 to 31%, is seen by some as a failure of non-operative management [20,21]. Thus, outcomes related to surgical removal of the appendix remain of great importance for surgeons, Emergency Medicine clinicians, Primary Care physicians, as well as patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…4 When considering and implementing methods for the standard of care, surgical intervention with an appendectomy is still the standard method of care if delaying the procedure could increase the in-hospital length of stay (H-LOS), the likelihood of later or recurrent hospital admissions, or more importantly, cause harm to the patient. 3 While there are systematic reviews and meta-analyses evaluating the difference in outcomes, rate of complications, and length of hospitalization between appendectomy and antibiotics, 1,[5][6][7][8][9][10][11] most of them have analyzed studies of varying qualities of evidence. The two reviews that have previously assessed Level 1 quality of evidence were limited in the number of studies included in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…While there are systematic reviews and meta-analyses evaluating the difference in outcomes, rate of complications, and length of hospitalization between appendectomy and antibiotics, 1,5-11 most of them have analyzed studies of varying qualities of evidence. The two reviews that have previously assessed Level 1 quality of evidence were limited in the number of studies included in the analysis.…”
Section: Introductionmentioning
confidence: 99%